2015
DOI: 10.1007/s12192-015-0632-x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic unpredictable stress (CUS) enhances the carcinogenic potential of 7,12-dimethylbenz(a)anthracene (DMBA) and accelerates the onset of tumor development in Swiss albino mice

Abstract: Social stressors evolving from individual and population interactions produce stress reactions in many organisms (including humans), influencing homeostasis, altering the activity of the immunological system, and thus leading to various pathological states including cancer and their progression. The present study sought to validate the effectiveness of chronic unpredictable stress (CUS) in cancer promotion and to assess oxidative stress outcomes in terms of various in vivo biochemical parameters, oxidative str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 57 publications
2
4
0
Order By: Relevance
“…Earlier studies from our laboratory have shown that CUS enhanced both the nephrotoxic and hepatotoxic potential of 7,12-dimethylbenz(a) anthracene in Swiss albino mice ( Suhail et al, 2011 ), by altering the oxidative stress and compromising the antioxidant system, thus stress may act as a promoter of carcinogenesis by enhancing the pro-oxidant potential of carcinogens. Moreover, CUS also aggravated the development of skin tumors (in terms of their incidence, tumor yield, and tumor burden) in mice which further strongly supported our studies on the effect of stress on cancer promotion through DNA damage and modulation of oxidant/antioxidant system in vivo ( Suhail et al, 2015 ). Thus, irrespective of the carcinogen used or the mode of application topical ( Suhail et al, 2011 , 2015 ) or oral as in the present study, CUS increased the toxic potential of the carcinogens.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Earlier studies from our laboratory have shown that CUS enhanced both the nephrotoxic and hepatotoxic potential of 7,12-dimethylbenz(a) anthracene in Swiss albino mice ( Suhail et al, 2011 ), by altering the oxidative stress and compromising the antioxidant system, thus stress may act as a promoter of carcinogenesis by enhancing the pro-oxidant potential of carcinogens. Moreover, CUS also aggravated the development of skin tumors (in terms of their incidence, tumor yield, and tumor burden) in mice which further strongly supported our studies on the effect of stress on cancer promotion through DNA damage and modulation of oxidant/antioxidant system in vivo ( Suhail et al, 2015 ). Thus, irrespective of the carcinogen used or the mode of application topical ( Suhail et al, 2011 , 2015 ) or oral as in the present study, CUS increased the toxic potential of the carcinogens.…”
Section: Discussionsupporting
confidence: 86%
“…One enzyme unit is defined as the amount of enzyme (Suhail et al, 2015) decomposing 1 μM H 2 O 2 per minute at 25°C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Yellowness(b)* values of the muscles of the THY and ORE groups were significantly reduced by 27.46% (P<0.05) and 24.38(P<0.05) compared to the control group (13.00). It might be that the essential oils have a function of antioxidant in laboratory studies (Suhail et al, 2015;Bi et al, 2016). It is reported that that the active ingredients of essential oils from Anoectochilus roxburghii can eliminate free radicals including 1,1-Diphenyl-2-picrylhydrazyl radical 2,2-Diphenyl-1-(2,4,6-trinitropheny l) hydrazyl (DPPH); 2, 2'-Azinobis-(3-ethylbenzthiazoline-6-sulphonate) (ABTS) and the superoxide anion (O2-) (Shao et al, 2014).…”
Section: Microbial Enumerationmentioning
confidence: 99%
“…Mice were randomly divided into CUMS (n=10) or control (n=10) groups after the in vivo implantation of tumor cells. The CUMS procedure was conducted as previously described [11][12][13] but adjusted slightly. Briefly, stress regimes were administered, consisting of the following eight stressors: food deprivation (24 h), water deprivation (24 h), tail pinch (5 min, 1 cm from the distal portion of the tail), cold swimming (3 min at 4°C), physical restraint (2 h), moist bedding (6 h), 30° cage tilt (12 h) and overnight stroboscopic lighting.…”
Section: Chronic Unpredictable Mild Stress Modelmentioning
confidence: 99%